Diagnostic challenge in children with an acquired demyelinating syndrome: an illustrative case report - Midaglia, Luciana; Felipe-Rucián, Ana; Delgado Alvarez, Ignacio; Montalban, Xavier; Tintoré, Mar (Frontiers in Neuroscience, 2023)
The clinical-radiological and biological overlap of the spectrum of paediatric demyelinating disorders makes the diagnostic process of a child with an acquired demyelinating syndrome truly challenging. We present a 9-year-old girl with subacute symptoms of severe decrease in bilateral visual acuity and gait ataxia. An urgent MRI showed inflammatory-demyelinating lesions affecting the periaqueductal grey matter, the cerebellar hemispheres, the area postrema as well as both optic nerves and chiasm.Likewise, multisegmental involvement of the cervical and dorsal spinal cord was found, with short and peripheral lesions. Anti myelin oligodendrocyte glycoprotein (MOG) antibodies (Abs) were positive in cerebrospinal fluid (CSF) and weakly in serum.Oligoclonal bands (OB) were positive in CSF. Based on all this, the diagnosis of MOG antibody disease (MOGAD) with a neuromyelitis optica spectrum disorder (NMOSD)-like picture was made. Given the good clinical and radiological recovery after the acute phase treatment, and that anti MOG Abs became negative, it was decided to keep the patient without specific treatment. However, during follow-up, while the patient was asymptomatic, a control brain MRI showed the appearance of new lesions with morphology and topography suggestive of multiple sclerosis (MS). This, added to the presence of OB, made the diagnosis of paediatric-onset MS (POMS)likely.Immunosuppressive treatment was restarted with a good response since then. Unlike adult-onset MS, children with POMS may usually not have entirely typical clinical and radiological features at presentation. In many cases, the time factor and close clinical and radiological monitoring could be critical to make an accurate diagnosis.